Successful treatment of cytomegalovirus enteritis after unrelated allogeneic stem cell transplantation by the infusion of ex vivo‐expanded CD4+ lymphocytes derived from the recipient's peripheral blood donor cells. Issue 1 (30th January 2016) - Muto, T.; Takeda, Y.; Tsukamoto, S.; Sakai, S.; Mimura, N.; Ohwada, C.; Takeuchi, M.; Sakaida, E.; Ota, S.; Iseki, T.; Shimizu, N.; Morio, T.; et al.
Abstract: Adoptive immunotherapies have been developed for antiviral agent‐refractory cytomegalovirus (CMV) disease after stem cell transplantation (SCT). However, the application of such strategies is limited, particularly in terms of need for donor cooperation regarding blood sampling and inaccessibility in the setting of cord blood transplantation. Herein, we describe the first successful treatment of antiviral agent‐refractory CMV enteritis after allogeneic SCT by the infusion of ex vivo ‐expanded donor‐derived CD4 + lymphocytes obtained from the recipient's peripheral blood.